Application of game model for stakeholder management in construction of ecological corridors: A case study on Yangtze River Basin in China. (May 2017) - Li, Feng; Pan, Bing; Wu, Yuzhe; Shan, Liping
Abstract: Disasters experienced by most countries are often caused by ecological crises. A worldwide consensus has been reached that building ecological corridors is the breakthrough solution for the phenomena. Developed countries rely on advanced science and technology and highly active social organizations to achieve remarkable results in ecological management. However, ecological management may not be as successful in developing countries because of the lack of development, imperfect social organizations, inadequate public awareness, and insufficient participation in environment-related issues. Ecological management is influenced by the synergy among governments, business enterprises, and the public. The cooperation issues faced by stakeholders in the construction of ecological corridors on Yangtze river basin in China have been rarely explored, and these issues present barriers to the promotion of ecological corridors. Therefore, this study investigates the significance of building ecological corridors along the Yangtze River Basin in China and analyzes the role of the stakeholders, specifically the local governments and construction companies. The Pareto optimality of the project is determined using a game model to ensure controlled and clean operations. This study proposes from the findings that developing countries should strengthen the cooperation among stakeholders, improve and stabilize the construction mechanisms for building ecological corridors, and increase public participation in the project. Highlights: Evaluated the changes of values of ecosystem service of Yangtze River Economic Belt. Investigated the significance of building ecological corridors' along the Yangtze River Basin in China. Analyzed the role of the stakeholders, specifically, the local government and construction company. Propose that developing countries should strengthen the cooperation between stakeholders.